PROMIS Ability to Predict Outcomes and Time to Surgery for Patients Treated with Bunion Surgery for Hallux Valgus - Chase Gauthier MD; Padam Kumar MD; Austin Paradis BS; Travis Dias BS; Thomas Ecker BS; Tyler Gonzalez MD, MBA; J. Benjamin Jackson MD, MBA (Foot & Ankle Orthopaedics)
Category: Midfoot/Forefoot; Bunion Introduction/Purpose: Patient-reported outcome metrics are useful in determining a patient’s clinical response to a given intervention. Despite their usefulness, few studies have identified the potential prognostic value of patient-reported outcome metrics. This study looks to evaluate whether preoperative PROMIS scores can predict time to surgery and improvement in postoperative PROMIS scores in those undergoing hallux valgus correction surgery. Methods: A retrospective review was conducted of patients undergoing surgical intervention for hallux valgus at a single academic institution between June 2020 and June 2023. Demographic information, time to surgery, PROMIS scores, and preoperative radiographic measurements were collected. The minimal clinically important difference (MCID) in PROMIS scores was defined as half of the standard deviation of the change in PROMIS scores. A total of 209 patients were included in the study. Categorical and continuous data were compared using the Chi-squared test and Student’s T-test, respectively. Multivariable logistic regression analysis was utilized to control for confounding variables. All p< 0.05 were considered statistically significant. Results: Higher preoperative pain interference (PI) (OR=1.3, p< 0.001), mobility (OR=1.22, p=0.003), and global health-physical (OR=1.14, p=0.043) scores were independent predictors for increased odds of achieving an MCID in PI score. Lower preoperative physical function (PF) (OR=1.18, p=0.007) scores and higher preoperative PI (OF=1.16, p=0.005) and global health-physical (OR=1.22, p=0.001) scores were independent predictors for increased odds of achieving an MCID in PF scores. No factors were independently associated with achieving an MCID in mobility scores. Finally, being seen first by an MD (OR=3.7, p=0.034) and being unmarried (OR=34.3, p=0.032) were both independent predictors for having surgery within 6 months of presentation. Hallux valgus and Intermetatarsal angles at presentation did not significantly influence either the ability to achieve an MCID in PROMIS scores or time to surgery. Conclusion: Worse preoperative PI and PF scores were independently associated with an increased likelihood of achieving an MCID in those respective scores when controlling for confounding variables. Additionally, the severity of a patient’s hallux valgus, based upon their radiographic measurements at presentation, did not significantly influence a patient’s postoperative outcomes or time to surgery. These results suggest that patients with more severe hallux valgus symptoms, but not necessarily more severe hallux valgus radiographic findings, are most likely to clinically improve following surgical intervention.